Preparation method of porous adsorbent particles, porous adsorbent particles, sampling device and application of porous adsorbent particles

By dissolving poly(2,6-diphenyl-p-phenylene) in an organic solvent medium and evaporating the solution droplets in air to form porous adsorbent particles, the existing adsorbent pores are solved and the problems of uneven pores of existing adsorbents and poor thermal stability at high temperatures are achieved, and more efficient adsorption performance and thermal stability are achieved.

CN119730954APending Publication Date: 2025-03-28KINGS COLLEGE INNOVATION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380060637.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-07-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing adsorbents based on poly(2,6-diphenyl-p-phenylene) are uneven in pore size and distribution, resulting in insufficient adsorption performance and poor thermal stability at high temperatures.

Method used

By dissolving the poly(2,6-diphenyl-p-phenylene) in an organic solvent medium, the solution droplets are left suspended without mechanical support, and the solvent is evaporated to form porous adsorbent particles. This method allows control of pore size and distribution, designing molecules targeting specific classes of molecules.

Benefits of technology

The obtained porous adsorbent particles have higher uniform pore size and distribution, significantly improve adsorption performance and maintain thermal stability at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005276721970000011
    Figure HDA0005276721970000011
  • Figure HDA0005276721970000021
    Figure HDA0005276721970000021
  • Figure HDA0005276721970000031
    Figure HDA0005276721970000031
Patent Text Reader

Abstract

The invention relates to a method for preparing porous adsorbent particles. The invention also relates to porous adsorbent particles and a sampling device comprising a plurality of said particles. The invention also relates to the use of the particles or of the sampling device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing porous adsorbent particles, the present invention also relates to porous adsorbent particles of poly(2,6-diphenyl-p-phenylene oxide), and a sampling device comprising a plurality of the particles, and the use of the particles or the sampling device. Background Art

[0002] To ensure air quality, it is necessary to monitor the airborne presence and concentration of chemical compounds, particularly volatile organic compounds. Other reasons why it may be desirable to monitor the presence of airborne compounds may include for scientific purposes, such as detection of explosives, narcotics, or collection of samples in space missions.

[0003] Particularly when the presence of multiple target compounds is expected or required to be monitored, it is common practice to collect the target compounds on a solid adsorbent contained in a sampling device such as a sampling tube. The material within the sampling device is then desorbed and analyzed in a suitable laboratory, which typically involves gas chromatography (GC).

[0004] The desorption of analytes from adsorbents is based on the principle that, at elevated temperatures, previously adsorbed species are released from the adsorbent. The desorption temperature should be high enough to extract all of the analyte, but should not be too high as this increases the risk of artifacts resulting from thermal degradation of the adsorbent.

[0005] A material very suitable for use as an adsorbent in combination with thermal desorption is based on poly(2,6-diphenyl-p-phenylene ether), also known as poly(2,6-diphenylphenol), PPPO or 3PO. In this application, this compound will mainly be referred to as PPPO. Products based on PPPO are commercially available. An example of it is the adsorbent product of Buchem BV, the Netherlands It is widely used as a column packing material for capturing volatiles from air (VOC) or liquids. It has been specified in the standard methods of EPA, NIOSH, ISO 2011 16000-6 (indoor air sampling), ISO 16017-1 (sampling and analysis of VOC) and EN 14338:2004, EU Regulation No.10 / 2011 (food simulants). Use of.

[0006] Contaminants are easily removed from PPPO adsorbents due to weak intermolecular bonding forces. PPPO-based adsorbents are particularly useful for analyzing high boiling point compounds such as alcohols, polyethylene glycols, diols, phenols, mono- and diamines, ethanolamines, amides, aldehydes, ketones, and chlorinated aromatic compounds. Measurements of parts per billion (ppb) and parts per trillion (ppt) levels are feasible using thermal desorption equipment.

[0007] Although currently available PPPO-based adsorbents perform well, the present inventors have observed that there is still room for improvement. Summary of the invention

[0008] In a first aspect, the present invention relates to a method for preparing porous adsorbent particles, comprising i) providing a solution of poly(2,6-diphenyl-p-phenylene oxide) in an organic solvent medium; ii) placing droplets of said solution in a state in which they are maintained in aloft without mechanical support via any physical contact; iii) evaporating said organic solvent medium while maintaining said solution in said state, at least until said solution is converted into particles in a semi-solid or solid state.

[0009] In a second aspect, the present invention relates to a PPPO-based porous adsorbent particle, which can be obtained by the method of the first aspect of the present invention.

[0010] In a third aspect, the present invention relates to a sampling tube comprising a plurality of porous adsorbent particles according to the second aspect of the present invention.

[0011] In a fourth aspect, the present invention relates to the use of the porous particles according to the second aspect of the present invention as an adsorbent in air collection. Therefore, the present invention also relates to the use of the sampling tube according to the third aspect of the present invention in air collection.

[0012] The present invention provides PPPO-based adsorbent particles having good accessible surface area and higher uniformity in pore size and distribution than the PPPO-based materials of the prior art, which indicates improved adsorption performance. That is, the prior art materials have very uneven pore size distribution and irregular structure, and the present invention allows to provide monodisperse, uniform and accurate pore arrays and particle sizes. In particular, the method of the present invention makes it possible to control pore size and distribution, which allows to design adsorbent particles to target specific classes of molecules to be adsorbed. In this regard, it should also be mentioned that the present invention allows to prepare particles with very small pores, which can be used to adsorb very small molecules, for example, selected from volatile organic compounds, C1-C5 hydrocarbons such as CH4, CO2, CO compounds. The porous adsorbent particles are thermally stable at high temperatures C or higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A schematic diagram of the preparation of particles of the present invention using suspended PPPO solution drops is shown.

[0014] Figure 2 The surface of a prior art PPPO adsorbent product having irregularly shaped surface and pores (A) and the surface of a particle of the present invention having a pore structure of uniform size and distribution (B) are shown.

[0015] Figure 3 An exemplary sampling tube according to the present invention is shown.

[0016] Figure 4 Shown are SEM images of PPPO particles prepared from a 0.5 w / w % PPPO solution in DCM that has been exposed to a temperature of 375° C. The entire particle is shown in the top image, an enlarged portion is shown in the bottom image, and no heat treatment and heat treatment at 375° C. for 4 hours in a nitrogen atmosphere are shown on the left and right, respectively.

[0017] Figure 5 Shown are SEM images of PPPO particles prepared from a 5 w / w % PPPO solution in DCM that has been exposed to a temperature of 375° C. The entire particle is shown in the top image, an enlarged portion is shown in the bottom image, and no heat treatment and heat treatment at 375° C. for 4 hours in a nitrogen atmosphere are shown on the left and right, respectively.

[0018] Figure 6 Shown is a porous array on a 20 μm x 20 μm surface area of ​​particles prepared from a 8 w / w % PPPO solution in DCM at 60% relative humidity (RH) (T = 21°C).

[0019] Figure 7 Shown is a porous array on a 20 μm x 20 μm surface area of ​​particles prepared from a 5 w / w % PPPO solution in DCM at RH 10% (T = 21°C).

[0020] Figure 8 Shown is a porous array on a 20 μm x 20 μm surface area of ​​particles prepared from a 5 w / w % PPPO solution in DCM at 80% RH (T = 21°C).

[0021] Fig. 9 Shown are (a) a series of SEM images of the surface structure of particles formed from a PPPO:DCM binary mixture (5 w / w% PPPO) by droplet suspension (T=21°C) at 40% RH, and (b) a series of SEM images of the surface structure of a film formed from a PPPO:DCM binary mixture (5 w / w% PPPO) deposited on a glass slide at the same RH (T=21°C) as the particles in (a).

[0022] Fig.10The SEM image sequence (T=21°C, RH=60%) showing the surface structure of the particles formed by the suspension. The vertical image shows the particles of the binary mixture of PPPO:DCM from the initial polymer concentration increased (0.5, 3, 5 and 8w / w%). The horizontal SEM image shows the particles formed by the ternary solution of 5w / w%PPPO, DCM and heptane, starting from 0w / w% heptane, and the initial heptane concentration increases (4, 6, 10, 14, 16w / w%).

[0023] Fig.11 A 3D plot is shown with the variables heptane concentration, PPPO concentration and RH represented by the x, y and z axes respectively and the intersection of the data sets is the initial binary solution concentration of 5 w / w % PPPO and RH %. Optical images of the final particles are shown along the axes and SEM micrographs are also shown for some particles showing trends in surface structure.

[0024] Figure 12 shows a scheme for estimating the particle surface area of ​​a particle according to the present invention. A) Particle dimensions; B) Image of a particle showing pores present in a layer within the skin; C) Image of a particle skin with pores appearing as multiple interconnected spheres. DETAILED DESCRIPTION

[0025] The present invention is based on the observation of the inventors that porous PPPO particles with improved properties can be obtained when droplets of PPPO dissolved in an organic solvent medium are placed in a state that keeps them in a state of suspension without mechanical support by any physical contact, and are maintained in this state to allow the majority of the solvent medium to evaporate. The inventors have found in particular that maintaining the PPPO solution in a state of suspension without mechanical support by any physical contact during the evaporation of the solvent medium allows the design and acquisition of adsorbent particles with a pore structure of uniform size and distribution. Figure 2 This effect is clearly shown in Figure 2 A shows the surface of a prior art PPPO adsorbent product having an irregularly shaped surface and pores, and wherein Figure 2 B shows the surface of a particle according to the invention having a pore structure of uniform size and distribution.

[0026] During the drying process of polymer solution droplets, the resulting particle size, shape and surface structure can be controlled, with an emphasis on the reliable and predictive design of particles with uniform, specific morphologies. In particular, the present invention allows the design and control of pore sizes ranging from very small to larger pores in order to specifically target the molecules to be adsorbed. In particular, the present invention allows the preparation of highly porous particles from polymer solutions with low concentrations of polymer, wherein the particles surprisingly do not collapse when exposed to high temperatures of 375°C or more. The applications of the adsorbent particles according to the present invention in sensors / adsorbers are wide-ranging.

[0027] The above-mentioned state that the solution is kept in the air without mechanical support via any physical contact can actually be suitably obtained by making the particles in a suspended state. In a practical embodiment, making the solution in the said state is achieved by suspending the solution in the air against gravity. In order to keep the solution droplets suspended, this will require an upward force that counteracts the weight of the solution so that the solution does not fall (accelerate downward) or rise (accelerate upward).

[0028] Although there are various techniques for placing objects in suspension and maintaining them in suspension, in practical embodiments, the solution can be suspended against gravity and maintained in the air by using a particle suspension technique, such as acoustic levitation. Acoustic levitation is a method of suspending a substance in the air against gravity using acoustic radiation pressure from high intensity sound waves. Alternative droplet suspension methods, such as spray drying techniques, can be used in the context of the present invention, as long as the suspended polymer solution is maintained in the air without mechanical support via any physical contact.

[0029] When particles are prepared in a drying process according to the present invention, the polymer aggregates at the surface of the droplet, reaches a critical concentration and forms a gel-like surface layer at the interface. The core of the droplet remains liquid for a period of time or longer. The solvent continues to evaporate through the surface layer, and depending on the thickness and shear modulus of the surface layer, a cavity is formed in the center of the droplet in due time. The formation of the cavity creates a pressure difference, which causes mechanical instability in the surface layer as the droplet further reduces its volume, thereby producing a hollow particle with a wavy surface structure. The method is as follows Figure 1 As shown, therein, as a non-limiting example, an acoustic levitator is used to prepare the particles of the present invention. Figure 1 Solvent evaporation, skin and cavity formation, and surface warping are shown. This ultimately results in polymer particles after drying over time by solvent evaporation.

[0030] The organic solvent is evaporated while the solution is kept in the state, at least until the solution is converted into particles in a semi-solid or solid state. Once the particles are in a semi-solid or solid state, conventional drying techniques can be used to evaporate the remaining liquid without changing their structure and morphology. This makes the production process more efficient. Therefore, preferably after step iii), the particles are collected and dried in step iv). The drying step can be suitably carried out by incubating the collected particles in an oven.

[0031] During the drying of the solution of PPPO in the organic solvent medium, the so-called self-assembly occurs. This is a spontaneous process that leads to the formation of a nano / micrometer honeycomb structure (pore array) by condensation of water droplets. The main physical processes involved in the formation of these arrays generally include 1) evaporation of the polymer solution; 2) water droplet nucleation; 3) condensation of water droplets; 4) droplet growth; 5) rearrangement and stabilization of droplets on the surface; 6) evaporation of water; and 7) solidification of the polymer, which produces a nano / micrometer porous honeycomb pattern, called a "breathing diagram". The inventors were surprised to find that despite being heated above the glass transition temperature, these porous arrays on the resulting particles can withstand high temperatures (up to 400°C) without losing the resulting particle structure. Typically, current PPPO-based adsorbents are used within this temperature range, meaning that the adsorbent particles according to the present invention can withstand suitable application temperatures while maintaining their fine structure. The best results were obtained by providing a solution of PPPO in the organic solvent medium in step i) at a concentration of at least 1% by weight, preferably at least 2% by weight, based on the weight of the solution. In this regard it is noted that wherever the notation of w / w % is used, this refers to the weight % of a given component based on the weight of the solution in which it is dispersed / dissolved.

[0032] The higher the concentration of PPPO in step i), the smaller the size and number of pores in the particles. On the other hand, when the concentration of the solution is very low, the surface layer of the particles formed when drying is very thin, which may adversely affect the stability of the particles. In view of this, it is preferred to provide a solution of PPPO in an organic solvent medium with a concentration of 0.5% w / w-20% w / w, wherein the optimized concentration is 2-8% w / w, such as 3-7% w / w, such as 4-6% w / w. On the one hand, between these ranges, a good balance is achieved between pore size and distribution and therefore adsorption capacity, and on the other hand, thermal and mechanical stability is improved. It is further preferred in this regard that the solution of PPPO in the organic solvent medium is provided at a concentration of about 5% w / w.

[0033] The relationship between the initial concentration of PPPO and the pore size and distribution also allows the particles to be designed to desired specifications with respect to pore size and distribution by varying the initial concentration of PPPO.

[0034] The solvent medium used for the PPPO solution may be a medium comprising a single solvent or comprising a mixture of solvents.

[0035] About the organic solvent medium of PPPO solution, when solution is based on dichloromethane (DCM), obtain good result.PPPO dissolves well in this solvent, and it can evaporate effectively.Other solvents that can be used based on its polarity and evaporation characteristics can be selected from chloroform, toluene and tetrahydrofuran (THF) without restriction.The inventor has observed that these solvents can dissolve PPPO, for obtaining particles according to the present invention.

[0036] The inventors have found that the surface structure and morphology of the particles can be further adjusted by using a ternary system of PPPO, a good solvent and a non-solvent using non-solvent induced phase separation (NIPS). A small amount of non-solvent can affect the pore size and distribution to the desired extent and can therefore be used to adjust the particles to the desired specifications with respect to pore size and distribution. As a good solvent, any of the above solvents can be used, and as a non-solvent, for example, heptane can be used. For the purposes of the present invention, a preferred solvent / non-solvent combination is DCM as solvent and heptane as non-solvent. Good results can be obtained with heptane at a concentration of up to 6% w / w, for example 4-6% w / w.

[0037] Placing the solution in suspension and maintaining the solution in suspension can be performed in an atmosphere with any relative humidity (RH), wherein it should be remembered that RH has an effect on the size and distribution of pores, as will be explained below. In this regard, any RH between 0-100%, for example 10-80%, is contemplated. Increasing the RH of the atmosphere in which the droplets are dried results in an increase in the extraction time, but also results in a larger final particle size. In this sense, RH can also be used to tailor the structure and morphology of the adsorbent particles. Higher RH means that more water condenses on the surface of the droplets during the drying process, and this, together with the complex internal and external flows, results in some water being trapped in the gelatinous surface layer as it develops. The resulting water capsules act in much the same way as the solvent-rich capsules, because they provide support and prevent the surface layer from wrinkling. As a result, the particles become more and more porous as the RH increases. On the other hand, a wide range of RH is suitable for the purposes of the present invention, because a porous array is formed at an RH as low as 10% or less, and pores with increasing size, stacking irregularities and polydispersity as the RH increases. For very small pores, RH below 10%, for example 0.1%-10%, may be used to allow design of the pores for C1-C2 hydrocarbon adsorption.

[0038] In a very suitable embodiment, suspending and maintaining the solution in suspension occurs in an atmosphere having a relative humidity of 50-70%, preferably about 60%. At these relative humidity levels, a very good balance is achieved between pore size and distribution, and thus good adsorption capacity, on the one hand, and increased thermal and mechanical stability, on the other hand.

[0039] Therefore, by changing the initial concentration of the PPPO solution, the relative humidity of the environment where evaporation occurs, the adsorbent particles can be designed according to the needs of the user. Similarly, the use of non-solvents can be applied to provide ternary solutions to adjust the morphology and surface of the PPPO adsorbent particles.

[0040] According to the present invention, no additional heating is required during steps ii) and iii), and the particle formation process can be conveniently carried out at room temperature. In this regard, although heating can be applied, the suspension and maintenance of the solution in suspension is suitably carried out at a temperature between 15°C and 25°C, preferably at room temperature (20-25°C).

[0041] As described above, the method of the present invention results in porous adsorbent PPPO particles which differ from the PPPO adsorbents of the prior art in that they have a higher uniformity in pore size and distribution than the PPPO-based materials of the prior art, which indicates improved adsorption performance. Therefore, in this respect, the present invention also relates to a porous adsorbent PPPO particle which can be obtained by a method according to the preceding claims. According to the above, the particles of the present invention may have a surface structure comprising a porous array.

[0042] In one embodiment, the particles are spherical particles having a porous PPPO surface layer with a thickness between 30 and 50 μm. Such particles can be obtained under the preferred method and conditions described above and have good mechanical strength.

[0043] The pores may suitably have an apparent pore radius R of 0.5 μm to 1 μm. ap and / or an average pore spacing R of 0.4 μm to 1 μm s , in order to achieve a good balance between pore size and distribution, and thereby a good balance between adsorption capacity (on the one hand) and increased thermal and mechanical stability (on the other hand).

[0044] To make the particles particularly suitable for adsorbing very small molecules, such as C1-C5 hydrocarbons, an apparent pore radius below 0.5 μm may be desirable, which can be engineered by increasing the PPPO concentration and / or decreasing the RH and / or adding a nonsolvent such as heptane.

[0045] The particles of the present invention can be used as adsorbents in air collection, especially in high temperature environments (due to their improved thermal stability). In this regard, the present invention also relates to the use of the particles of the present invention as adsorbents in air collection. In particularly suitable embodiments, the adsorbent particles of the present invention can be used to adsorb volatile organic compounds and / or C6-C26 hydrocarbons. On the other hand, the present invention also provides particles that allow the capture of very small molecules (if the particles are designed to have very small pore sizes). Therefore, instead of particles that adsorb a wide range of these molecules, the specific morphological design of the pore size and structure allows the preparation of particles for targeted capture of specific molecules or within a narrow distribution range of C1-C26.

[0046] In practical applications of the present invention, the adsorbent particles of the present invention are used in a sampling tube. Therefore, the present invention also relates to a sampling device, which comprises a plurality of porous adsorbent particles according to the present invention. In practice, a sampling tube is suitable for use as a sampling device. Figure 3 An exemplary embodiment of such a tube is shown. Figure 3 The sampling tube of is composed of a glass tube 1, which contains a certain amount of adsorbent particles 2. In order to provide a uniform pressure drop, glass wool 3 and foam separators 6 can be used. The tip 5 of the tube can be precisely sealed to allow safe and easy breaking to the desired opening size. The sealing cap 4 prevents contamination.

[0047] In a preferred embodiment, the sampling tube is a thermal desorption (TD) tube. PPPO is a well-known adsorbent for thermal desorption techniques. In addition, the high thermal stability of the particle material allows desorption at very high temperatures. In this way, complete desorption of any adsorbed analyte is ensured without the risk of artifacts originating from thermal degradation of the adsorbent particles. DETAILED DESCRIPTION

[0049] Example

[0050] The following examples are included to illustrate the invention and not to limit the scope of the claims.

[0051] Example 1: General preparation of particles

[0052] This section includes a description of the process steps and features that apply to all PPPO particle production routes. In subsequent sections, changes to specific parameters are included to achieve certain structures.

[0053] 1.1. Chemicals

[0054] Poly(2,6-diphenyl-p-phenylene ether) (PPPO) (reported by M n 11-250 kg / mol), dichloromethane (DCM, VWR Chemicals, 99.9%, ρ = 1.33 g / cm 3) and heptane (VWR Chemicals, 99.8%, ρ = 0.67 g / cm 3 ) were used as solvent and non-solvent, respectively.

[0055] 1.2. Acoustic levitation and imaging

[0056] For the current experimental demonstration, a uniaxial acoustic levitator based on a relative array of ultrasonic transducers (TinyLev) was used for droplet drying experiments, all of which were conducted under controlled RH (RH chamber from Coy Labs, used in conjunction with an Electrotech Systems microcontroller). A horizontal tube microscope equipped with a 5X objective and a Basler acA2040-90uc camera was used for image acquisition, with backlighting illuminating the suspended droplets to enhance image contrast. The small field of view of the camera was adjusted to align with the central pressure node of the standing wave, meaning that a syringe could be used to accurately place polymer solution droplets at the point where they would be supported by acoustic forces. At a rate of 1 FPS during drying, images were obtained within 5 minutes for polymer solution droplets and pure solvent droplets, as long as they were completely evaporated. Images were analyzed using open source image analysis software (ImageJ). The dried polymer particles were coated with gold and imaged in a Zeiss Auriga Crossbeam scanning electron microscope (SEM).

[0057] 1.3 Preparation of the particles according to the invention

[0058] For the experiments shown in the Examples section of the present invention, the following general procedures were performed.

[0059] Step 1. Using a 1 mL HENKE-JECT syringe and a 23-gauge needle at room temperature (21°C), deposit approximately 1.5 × 10 - 3 mL of PPPO in DCM and leave it hanging.

[0060] Step 2. The solution was suspended in situ for 5 minutes to allow sufficient removal of the DCM, thereby ensuring that the particles were concentrated to at least a "gel-like", ie, semi-solid, state and that the structure did not evolve further.

[0061] Step 3. Additional solvent removal beyond this point was very slow and the particles were collected in a glass vial (but not sealed as there was still solvent left) and left for at least 24 hours to dry.

[0062] Step 4: The 'dry' pellets at this point will still contain some trapped DCM and are placed in an oven at 40°C for about 12 hours to facilitate additional solvent removal (DCM boiling point is 39.6°C).

[0063] Example 2. Particles prepared with low concentration PPPO (heat treatment)

[0064] For this example, particles were prepared from a 0.5 w / w % PPPO solution in DCM. The relative humidity of the atmosphere was set to 60% for room temperature (21°C). -3 mL of PPPO solution in DCM (concentration 0.5 w / w%) was suspended. Figure 4 SEM images of these particles are shown. Figure 4 As shown in the left image of , particles prepared in this way have a "coral"-like morphology. The entire particle is shown in the top image and a zoomed portion is shown in the bottom image.

[0065] When the particles were subjected to heat treatment at 375°C for 4 h in a nitrogen atmosphere, it seemed that the particle structure could not withstand the heat treatment, as the structure of the particles changed significantly, as can be seen by comparing the left image (no heat treatment) and the right image (heat treatment).

[0066] Figure 4 The 0.5 w / w% particles in have a very complex structure before heat treatment that appears to consist of a series of surface undulations: the concave parts of the surface are thin folds of wrinkled paper polymer, while the convex parts contain "coral"-like structures. The fine details of these structures are lost after heating, and small pores remain in the "coral" areas because the openings are apparently significantly plasticized before crystallization. In contrast, in the concave areas, the openings become larger because the very thin polymer matrix has broken and merged as it plasticized to leave the "chewing gum" structure. The particles themselves appear to shrink and collapse.

[0067] Example 3. Particles prepared with 5% w / w concentration of PPPO (heat treated)

[0068] For this example, particles were prepared from a 5 w / w% solution of PPPO in DCM. Other conditions were as described in Example 2.

[0069] Figure 5 SEM images of these particles are shown. The entire particle is shown in the top image, and a zoomed portion is shown in the bottom image. Figure 5 As can be seen in the lower left image of , particles having a surface comprising a porous array were obtained. When the particles were exposed to a heat treatment at 375°C and a nitrogen atmosphere for 4 h, it seems that the particle structure can withstand the heat treatment, as the structure of the particles did not change significantly, as can be seen by comparing the left image (no heat treatment) and the right image (heat treatment). On the other hand, the 5 w / w% polymer had an almost unchanged structure ( Figure 5). The pore size is about the same before and after heating (perhaps slightly smaller after heating due to some plasticization). Apparently, due to the higher concentration of PPPO, the thicker polymer skin is apparently strong enough to maintain its structure long enough to allow crystallization to occur. Thus, in the particles exposed to heat treatment at 375°C for 4 hours under nitrogen atmosphere, the morphology did not change much during this heat treatment, indicating that these particles are able to withstand high temperatures for a long time.

[0070] Example 4

[0071] For this example, particles were prepared from a solution of 8 w / w% PPPO in DCM. The relative humidity of the atmosphere at room temperature (21°C) was set to 60%. -3 mL of PPPO solution in DCM (concentration 8 w / w%) was suspended.

[0072] This produces particles with a porous array structure, e.g. Figure 6 As shown in FIG. 1 , it shows a porous array on a 20 μm × 20 μm surface area of ​​the particle. Figure 6 As shown, the pores are uniform in size but not densely packed.

[0073] Example 5

[0074] For this example, particles were prepared from a solution of 8 w / w% PPPO in DCM. The relative humidity of the atmosphere at room temperature (21°C) was set to 10%. -3 mL of PPPO solution in DCM (concentration of 5 w / w%) was suspended.

[0075] This produces particles with a porous structure, e.g. Figure 7 As shown in FIG. 1 , it shows a porous array on a 20 μm × 20 μm surface area of ​​the particle. Figure 7 As shown, compared with the pores of the particles of Example 4 ( Figure 6 ), the pores are relatively small.

[0076] Example 6

[0077] For this example, particles were prepared from a 5 w / w% solution of PPPO in DCM. The relative humidity of the atmosphere was set to 80% at room temperature (21°C). -3 mL of PPPO solution in DCM (concentration of 5 w / w%) was suspended.

[0078] This produces particles with a porous array structure, e.g. Figure 8 As shown in FIG. 1 , it shows a porous array on a 20 μm × 20 μm surface area of ​​a particle. Figure 8As shown, the pores are relatively large compared to the pores of the particles of Examples 4 and 5 ( Figure 5 and 6 ).

[0079] The results of Examples 4, 5 and 6 show that relative humidity and initial PPPO concentration affect the final morphology of the particles and can therefore be used to adjust the particles to the desired specifications.

[0080] It was also observed that increasing the initial PPPO concentration of the droplets resulted in increased extraction times and final particle sizes. As the PPPO concentration increased, the concentration of polymer aggregated on the droplet surface became higher and produced a thicker surface layer that was more resistant to deformation - since this thick surface layer restricted diffusion, the total extraction time of the solvent also increased with PPPO concentration.

[0081] Example 7. Comparison between adsorbent materials formed into films and particles.

[0082] The particles prepared according to the invention were compared with adsorbent materials prepared from membranes. For this purpose, the particles according to the invention were prepared from a solution of 5 w / w% PPPO in DCM. The relative humidity of the atmosphere was set to 80% at room temperature (21° C.). Approximately 1.5×10 -3 mL of PPPO solution in DCM (concentration 5 w / w%).

[0083] On the other hand, to prepare adsorbent materials from membranes, 5 w / w% PPPO:DCM solutions were drop cast on glass microscope coverslips and dried at 40% RH. The dried membranes were painted gold and imaged in a Zeiss Auriga Crossbeam scanning electron microscope (SEM).

[0084] Fig. 9 is a SEM image of the porous array on the surface of particle (A). Fig. 9 As shown, a porous array is formed that is uniform in size, relatively uniform, and densely packed. On the other hand, when the polymer solution is dried into a membrane, under these conditions the pores are less uniform in size and less uniformly packed, as shown in Fig. 9 B. Note that the pores formed at higher RH (60, 80 and 100%) are very similar in size, shape and packing for both the particles and the corresponding deposited films (not shown), but even so, the films of adsorbent material are not well suited for the primary intended use in coupons.

[0085] Example 8. Use of non-solvent in PPPO solution

[0086] In this example, the use of non-solvent heptane was tested in PPPO solutions. The surface structures of particles formed from binary PPPO:DCM and ternary PPPO:DCM:heptane solutions are shown in Fig.10 In the SEM images of . The composition is shown in the upper right corner of each image with vertical (increased PPPO) and horizontal (increased heptane). First, the structure from the binary solution (from top to bottom, especially at higher concentrations), including honeycomb cavities that do not seem to be interconnected. Since there is no non-solvent during the drying process, the porous array must be the source of this porosity. As mentioned above, the pores on the lowest concentration (0.5w / w%PPPO) particles are less isotropic in shape and seem to be less uniform in size, resulting in a "coral-like" structure. The pores formed by higher concentrations of PPPO (3, 5 and 8w / w%PPPO solutions) seem to have wider, more random spacing.

[0087] The structure of the particles from PPPO:DCM:heptane at low initial heptane concentrations (4 and 6 w / w%) does not appear to be formed by stratification, and uniform small units are characteristic of breath pattern formation. Therefore, by examining the surface structure alone, it seems that these small amounts of non-solvents are not sufficient to cross the phase boundaries during the drying process. It seems that with this ternary system, the initial surface layer formation occurs early and the breath pattern is the main structure because the surface layer does not reach concentrations within the two-phase region, but the changes in the internal composition depend on the ability of each solvent to diffuse through the gel-like PPPO surface layer. In this case, heptane seems to be greatly restricted by the PPPO skin layer, causing the internal liquid composition of the drying droplets to experience NIPS. Higher heptane compositions (above 6% w / w) form typical stratified structures with large pores and lower uniformity, and at the highest composition, with a nodular surface.

[0088] For the heptane containing solution, particle size also increases with initial heptane concentration, although for different reasons. Since DCM evaporates several times faster than heptane, the concentration drop within the polymer solution droplet may enter the two-phase region at some point and begin to separate, especially near the interface because there is higher polymer aggregation. This phase separation will result in pockets of solvent-rich phase, which will evaporate and form air pockets that will effectively support the polymer skin and prevent particle wrinkling - resulting in larger final particles. In addition, with the addition of heptane, the extraction time decreases because these pockets of solvent-rich phase near the surface will evaporate faster because they contain less polymer.

[0089] Example 9

[0090] The above examples show the formation of suspended PPPO particles.

[0091] By varying the polymer concentration, heptane concentration and by using RH to induce pore formation, a range of particle morphologies, sizes, skin thicknesses, surface structures and surface porosities can be controllably formed. Fig.11 A summary of findings in this regard is shown.

[0092] Increasing the initial PPPO concentration of the droplets resulted in increased extraction time and final particle size. As the PPPO concentration increased, the concentration of polymer aggregated on the droplet surface became higher and produced a thicker surface layer that was more resistant to deformation.

[0093] Fig.11 SEM images of particles from binary PPPO solutions are shown, which show the formation of pores on all particle surfaces, even to some extent on particles prepared with a starting solution of 0.5% w / w PPPO.

[0094] Fig.11 It was also shown that a hierarchical structure was seen on the polymer surface above 6 w / w % heptane concentration, below which a porous array was seen on the surface.

[0095] like Fig.11 It is further shown that pores form on the suspended droplets at RH as low as 10%, with increasing pore size, packing irregularities, and polydispersity as RH increases.

[0096] Example 10. Estimation of particle area

[0097] In the following examples, the surface area of ​​the particles according to the invention was estimated as evidence of the high adsorption capacity of the particles according to the invention.

[0098] To this end, Figure 5 The particles (Example 3) were used as a model.

[0099] By Fig. 12A The final particles shown were modeled as approximately oblate ellipsoids to determine particle size; assuming no pores, the average particle surface area formed at 5 w / w% PPPO was ~3,200,000 μm 2 The measured surface thickness is 40 μm.

[0100] based on Figure 5 The average pore radius is estimated to be R = 0.75 μm and the average pore spacing is estimated to be R S =0.6μm.

[0101] Assuming each pore is a cylinder, its length corresponds to the surface thickness of the particle (40 μm). The average pore circumference is 2×π×0.75=4.71 μm. The average pore area is 4.71×40=188.50 μm2 The measured pore coverage is 47%, so the "void space" is 53%. Therefore, the approximate particle surface area is:

[0102] (3200000×0.53)+(3200000×0.47×188.5)=285000000μm 2 , which means that the surface is increased by about 90 times.

[0103] Alternatively, assuming that the pores are spheres and taking the average apparent pore radius to be R = 0.75 μm and the average pore spacing to be R S = 0.6 μm. The average pore internal area will be 32.52 μm 2 .

[0104] The measured pore coverage is 47%, so the "void space" is 53%. Therefore, the approximate particle surface area is: (3200000 x 0.53) + (3200000 x 0.47 x 32.52) = 50600000 μm 2 . This means that the surface area increases by about 15.8 times.

[0105] Further reference to this point, from Fig. 12B It can be clearly seen that the pores exist in layers within the surface layer. Now assume that the particle has a surface layer thickness of 40 μm and a pore size of about 2 μm, and assume that the pores in the surface layer are interconnected spheres in the multilayer sphere, as Fig. 12C Shown schematically, this would result in the following figures:

[0106] Table 1. Estimated surface area increase of particles according to the invention.

[0107] Number of layers <![CDATA[Effective adsorption area (μm 2 )]]> Surface area increase times 5 468800000 146.5 10 928300000 290.1 20 1847300000 577.3

[0108] By modeling the pores as cylinders or spheres, surface area increases between 90.0 and 577.3 can be obtained when particles are prepared according to Example 3, and further adjustments according to the disclosure of this application can lead to even higher surface area increases.

Claims

1. A method for preparing porous adsorbent particles, comprising: i) providing a solution of poly(2,6-diphenyl-p-phenylene ether) in an organic solvent medium; ii) placing a droplet of said solution in a state wherein it is maintained in a suspended state without mechanical support via any physical contact; iii) evaporating the organic solvent medium while maintaining the solution in the state, at least until the solution is converted into particles in a semi-solid or solid state.

2. The method according to claim 1, wherein placing the solution in said state is achieved by suspending the solution in air against gravity.

3. The method of claim 2, wherein the solution is suspended and maintained in air against gravity using a particle suspension technique.

4. A method according to any one of the preceding claims, wherein the particle suspension technique is acoustic levitation.

5. A method according to any one of the preceding claims, wherein the solution of poly(2,6-diphenyl-p-phenylene ether) in the organic solvent medium is provided at a concentration of 0.5 to 20% w / w.

6. The method of claim 5, wherein the solution of poly(2,6-diphenyl-p-phenylene ether) in the organic solvent medium is provided at a concentration of at least 1% w / w.

7. The method of claim 6, wherein the solution of poly(2,6-diphenyl-p-phenylene ether) in the organic solvent medium is provided at a concentration between 1% w / w and 8% w / w.

8. The method according to claim 7, wherein the solution of poly(2,6-diphenyl-p-phenylene ether) in the organic solvent medium is provided at a concentration of about 5% w / w.

9. A process according to any one of the preceding claims, wherein the solvent medium is a dichloromethane based solvent medium.

10. The process according to claim 9, wherein the solvent medium further comprises heptane in a concentration of up to 6% w / w.

11. The method according to any one of the preceding claims, wherein bringing and maintaining the solution in said state is carried out in an atmosphere having a relative humidity of 10% to 80%.

12. The method according to claim 11, wherein suspending and maintaining the solution in said state is carried out in an atmosphere having a relative humidity of 50-70%, preferably about 60%.

13. The method according to any one of claims 1 to 10, wherein suspending and maintaining the solution in the state is performed in an atmosphere having a relative humidity of less than 10%.

14. The method according to any one of the preceding claims, wherein suspending and maintaining the solution in said state is performed at a temperature between 15°C and 25°C, preferably at room temperature (20-25°C).

15. A method according to any one of the preceding claims, wherein after step iii), the particles are collected and subjected to iv) Drying.

16. The method according to claim 15, wherein step iv) is performed by incubating the collected particles in an oven.

17. Porous adsorbent particles obtainable by a process according to the preceding claim.

18. The porous adsorbent particle according to claim 17, having a particle surface with a porous array.

19. The porous adsorbent particle according to claim 17 or 18, which is a spherical particle having a porous poly (2,6-diphenyl-p-phenylene oxide) surface layer with a thickness between 30 and 50 μm.

20. The porous adsorbent particle according to claim 17 or 18, wherein the pores have an apparent pore radius R between 0.5 μm and 1 μm. ap .

21. The porous adsorbent particle according to any one of claims 17 to 20, wherein the pores have an average pore spacing R of 0.4 μm to 1 μm. s .

22. A sampling device comprising a plurality of porous adsorbent particles according to any one of claims 17 to 21.

23. The sampling device of claim 22, which is a thermal desorption (TD) tube.

24. Use of the porous particles according to any one of claims 17 to 21 as adsorbent in air collection.

25. Use according to claim 24 for the adsorption of volatile organic compounds and / or C1-C26 hydrocarbons.

26. The use according to claim 24 or 25, for the adsorption of one or more selected from volatile organic compounds, C1-C5 hydrocarbons such as CH4, CO2, CO.